Analysis of Financial Technology Adoption, Financial Literacy, and Ease of Transactions on the Financial Satisfaction of E-Commerce Consumers in Central Java - Hildawati Hildawati; Rival Pahrijal; Paramita Andiani (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the influence of financial technology application, financial literacy, and ease of transactions on the financial satisfaction of e-commerce consumers in Central Java. A quantitative approach was employed using survey data collected from 150 respondents through a structured questionnaire measured on a Likert scale. Data analysis was conducted using SPSS version 25, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that financial technology application has a positive and significant effect on financial satisfaction, showing that the use of digital payment systems enhances efficiency and consumer confidence. Financial literacy also demonstrates a significant positive influence, suggesting that consumers with better financial understanding tend to make more responsible financial decisions and experience higher satisfaction. Ease of transactions emerges as the most dominant factor affecting financial satisfaction, highlighting the importance of user-friendly and efficient payment processes in e-commerce environments. Simultaneously, all independent variables significantly influence financial satisfaction, with the model explaining 61.0% of the variance. These findings imply that improving digital financial services, strengthening financial literacy, and enhancing transaction convenience are essential strategies for increasing consumer financial well-being in the digital economy⁠.